2017
DOI: 10.3345/kjp.2017.60.9.273
|View full text |Cite
|
Sign up to set email alerts
|

Update of minimally invasive surfactant therapy

Abstract: To date, preterm infants with respiratory distress syndrome (RDS) after birth have been managed with a combination of endotracheal intubation, surfactant instillation, and mechanical ventilation. It is now recognized that noninvasive ventilation (NIV) such as nasal continuous positive airway pressure (CPAP) in preterm infants is a reasonable alternative to elective intubation after birth. Recently, a meta-analysis of large controlled trials comparing conventional methods and nasal CPAP suggested that CPAP decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 66 publications
1
27
0
1
Order By: Relevance
“…This is because the risk of airway and lung injury and respiratory tract infection, which is commonly associated with invasive mechanical ventilation, is relatively low in noninvasive ven tilation 19) . However, if neonates who received only noninva sive As observed in previous studies 10,11) , the rate of application of mechanical ventilation was significantly reduced by the LISA method in this study; that is, it was lower in the MIST group than in the control group. Tomar et al 22) published a study using .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This is because the risk of airway and lung injury and respiratory tract infection, which is commonly associated with invasive mechanical ventilation, is relatively low in noninvasive ven tilation 19) . However, if neonates who received only noninva sive As observed in previous studies 10,11) , the rate of application of mechanical ventilation was significantly reduced by the LISA method in this study; that is, it was lower in the MIST group than in the control group. Tomar et al 22) published a study using .…”
Section: Discussionsupporting
confidence: 59%
“…To date, there have been many studies on preterm infants with a gestational age of 24 to 29 weeks who were diagnosed with RDS and were administered surfactant by MIST 10) . However, few studies have reported on moderately preterm infants, late preterm infants, and term infants in whom RDS was treated via…”
Section: Introductionmentioning
confidence: 99%
“…While the e cacy of surfactant therapy has been reported to improve respiratory function in late preterm infants with RDS [26][27][28], surfactant administration by minimally invasive methods is still being investigated in this population. The LISA method via thin catheter is widely adapted in Europe [29] and is a recommended method of care according to the latest consensus guidelines [9,12,30]. However, there is still large variability in the application of this technique regarding patient population that may bene t from this approach; the catheter type, the adequate dose and type of surfactant; the use of premedication; and the need of pharmacologic sedation during the procedure [31].…”
Section: Discussionmentioning
confidence: 99%
“…INSURE (INtubate, SURfactant , Extubate) strategy was evolved in Scandinavian countries that minimized the duration of ventilation post intubation and surfactant administration to four to six minutes and continuation of baby on noninvasive support and this significantly reduced the need for mechanical ventilation [7][8][9]. Further evolution of this towards avoiding the airway injury led to the introduction of MIST (minimally invasive surfactant therapy) and this has been widely assimilated in clinical practice by European neonatologists [10][11][12][13][14]. We introduced MIST for surfactant delivery in our neonatal units in Dubai in 2018 and have published our initial experience of the first three cases in 2018 [15] and subsequently our experience with 2.0 endotracheal tube (ETT) as an improvized novel technique for MIST in 2019 [16].…”
Section: Introductionmentioning
confidence: 99%